Computational Study of Traveling Wave Solutions of Isothermal Chemical Systems. (17th May 2016) - Qi, Yuanwei; Zhu, Yi
Abstract: This article studies propagating traveling waves in a class of reaction-diffusion systems which model isothermal autocatalytic chemical reactions as well as microbial growth and competition in a flow reactor. In the context of isothermal autocatalytic systems, two different cases will be studied. The first is autocatalytic chemical reaction of order m without decay. The second is chemical reaction of order m with a decay of order n, where m and n are positive integers and m > n ≥1. A typical system in autocatalysis is A +2 B →3 B and B → C involving two chemical species, a reactant A and an auto-catalyst B and C an inert chemical species. The numerical computation gives more accurate estimates on minimum speed of traveling waves for autocatalytic reaction without decay, providing useful insight in the study of stability of traveling waves. For autocatalytic reaction of order m = 2 with linear decay n = 1, which has a particular important role in chemical waves, it is shown numerically that there exist multiple traveling waves with 1, 2 and 3 peaks with certain choices of parameters.